Aplikasi Biochar dan Kompos Terhadap Peningkatan Hasil Tanaman Jagung (Zea Mays L.) - Petrus Kaliang Lelu; Yohanes Parlindungan Situmeang; Made Suarta (GEMA AGRO, 2018)
This study aims to determine the effect of biochar dosage and compost fertilizer and its interaction on the growth and yield of corn crops. This experiment used a randomized block design (RBD) with a factorial pattern consisting of 2 factors. The first factor was the dose of biochar (B) consisting of 4 levels, namely: 0 ton ha-1 (B0), 5 ton ha-1 (B1), 10 ton ha-1 (B2), 15 ton ha-1 (B3). The second factor is the dosage of compost fertilizer (K) consisting of 2 levels: 0 ton ha-1 (K0), and 20 ton ha-1 (K1). The results showed that the interaction between the treatment of biochar dose and compost fertilizer had no significant effect on all observed variables. Biochar and compost treatment have significant effect to most observed variables, except on leaf area and harvest index have no significant effect. Treatment of biochar with a dose of 10 ton ha-1 gave the highest dry kiln seedlings weight of 7.83 tons increased by 35.60% compared to the lowest dose without biochar of 5.77 tons. Treatment of compost doses of 20 ton ha-1 gave the highest dry seed oven per hectare weight of 7.42 tons increased by 16.60% when compared with the lowest yield on treatment without compost dose as much as 6.37 tons.